Analisis Sanggit Lakon Baratayuda Ki Joko Santosa - Timbul Subagya (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2008)
The term of sanggit in Surakarta puppetry is well known and its existence cannot be separated. For the reason, a dalang should prepare sanggit lakon which will be presented when he would like to have performance because garap sanggit produces certain effect to the audiences. In Javanese view, lakon Baratayuda is still believed to be sacred for it has strong magic. That is why a dalang who would like to perform Baratayuda should be careful in making sanggit lakon that will be presented. Joko Santoso is one pf the dalang who often present lakon Baratayuda. How his sanggit lakon is and he is always constant or not in his presentation. This article would like to explain one of his sanggit is presenting Baratayuda for bersih desa in Turus Polanharjo, Klaten in 2002.Keyword : Baratayuda, sanggit lakon